Validation of the mental health literacy questionnaire (MHLQ) among undergraduate students in Malaysia - Low, Kah Yue (2023)
Mental health literacy (MHL) is crucial to recognising, managing, and preventing mental illnesses. However, the study values of MHL studies in Malaysia have been limited as most findings are derived from instruments that have not been properly validated. To provide a validated MHL instrument, this study aimed to examine the suitability of the Mental Health Literacy questionnaire (MHLq) among Malaysian undergraduate students. Study 1 employed a cross-sectional survey to examine the factor structure of the MHLq with 618 undergraduate students. The sample was split randomly into two halves for exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). From EFA results, 12 items with the highest factor loadings were retained. CFA results confirmed the first-order four-factor structure with one error covariance of the 12-item MHLq among other competing models (i.e., the one-factor model and the second-order model with one general factor and four first-order factors). Study 2 recruited new samples to verify the model revealed in Study 1 and examine the MHLq-12’s validity. Consistent with Study 1, CFA results showed that the first-order four-factor structure fit the data, and all 12 items were significant. Most MHLq-12 subscales displayed Cronbach’s alpha values of less than 0.7, while ICC values supported their test-retest reliability. iii Results did not support the convergent validity of most MHLq-12 subscales with average variance extracted values below 0.5. Divergent validity was established by a low correlation between MHLq-12 and health literacy measured by HLS-SF12. Most MHLq-12 subscales showed limited evidence for predictive validity on help-seeking and positive mental health. In summary, current findings suggested the potential utility of a brief MHL instrument and discussed reevaluating existing theoretical frameworks for MHL. Modifications on the identified items are recommended to align with the understanding of MHL in the Malaysian context.